Rice Straw Composting Improves the Microbial Diversity of Paddy Soils to Stimulate the Growth, Yield, and Grain Quality of Rice - Huang, Xingchen; Wang, Hong; Zou, Yuning; Qiao, Cece; Hao, Bing; Shao, Qingqin; Wu, Wenge; Wu, Hua; Zhao, Jianrong; Ren, Lantian (Sustainability, 2023)
This study aimed to explore the effects of straw compost with different proportions as replacement to chemical fertilizer on soil microorganisms as well as rice growth yield and quality. The rice variety Quan9you 063 in Fengyang, Anhui province was employed as the research subject. Four experimental treatments were set: local conventional fertilization as a control (CK) and compost substituting chemical fertilizer at 10% (T1), 20% (T2), and 30% (T3) to investigate the effects of straw composting. Our findings revealed that T1 treatment had the best rice yield-increasing effect (p < 0.05). Compared with CK, the rice yield, grain number per panicle, and rice polishing rate increased by 6.43%, 21.60%, and 0.47%, respectively; the chalkiness and chalky grain rate decreased by 25.77% and 55.76%, respectively. The T1 treatment achieved significantly higher relative abundance of β-Proteobacteria, Sideroxydans, Methanoregula, and Candidatus Nitrosocosmicus, indicating that the compost replacing 10% chemical fertilizer notably increased the microbial diversity. Hence, the replacement of 10% of chemical fertilizers with compost can enhance the rice yield.